Experimental Study on Durability of IGU Sealant Constructions - B. Weller (Challenging Glass Conference, 2016)
The saving of energy has been an important topic for the last years. However, not only for building constructions but also in the field of naval architecture the energy revolution affected the used materials. Insulation glass units (IGU) are used on ships, because of their increased thermal insulation value, but their known problem of durability remains. Already after a few years, naval insulating glass units fog up on the inner site of the glass panes and get unusable. The insulating glass units are exposed to higher stress in the naval environment compared with building constructions. We have to consider comparatively high wind loads that results in thick glass packages. The dead weight of the outer panes are usually transferred via the edge sealant. Structural Sealant Glazing Systems (SSGS) without mechanical self-weight support are commonly used. Furthermore, there is the contact with saline water and high UV-radiation. Because of the movement of the ships around the world, the climatic load assumptions for stationary buildings do not apply. All these loads cause a pillow effect and stress the edge sealant to a point of an increased moisture transfer into the cavity. We conducted two-month artificial ageing tests according to DIN EN 1279-2. The experimental investigation included 67 insulating glass units and reference specimens, which are composed of 4 mm fully tempered glass and 12 mm cavity between the panes. The scope included bent and connected spacers, a variety of secondary sealant systems with an emphasis on novel permanent pressure equalisation structures. After the tests, it was possible to compare the moisture penetration of different edge sealant systems. Furthermore, we compared the aged with reference insulating glass units. We used these data to analyse the impact of the artificial ageing program on the sealants durability. The experimental investigation shows that the climatic loads have a strong influence on the gas transfer through the edge sealants of the insulating glass units. Systems, which enable the insulating glass unit to connect the gas cavity with the ambient air, absorb less moisture compared with reference systems. The results will allow us to evolve more durable sealant systems. Additionally, we can optimise the artificial ageing program for marine glazing products.